(untitled) (Research, Society and Development, 2022)
The Tutored Study Plan (PET) is a material developed by the State Department of Education of Minas Gerais, it is a material for free distribution that was adopted by the non-presential Teaching Regime, offered to students of the public education network during the pandemic period. In this sense, the present work aims to evaluate the quality of the PET and its applicability to the teaching of science and biology. The material was analyzed and categorized according to the applicability regulations in addition to issues related to practical teaching, addressing qualifications provided for in the National Common Curricular Base (BNCC), use in the public network, the context of pedagogical practice by investigation and the lack of classes practices, an essential element for the knowledge of science and biology. We conclude that the material meets the need for remote emergency teaching, but it still has negative points, such as the absence of practical classes and regional issues in its construction, and a readjustment in the material according to the curricula is indicated.